Salt mixtures induce anatomical modifications in the halophyte Prosopis strombulifera (Fabaceae: Mimosoideae) - Reginato, Mariana Andrea (2015)
Plant morphology, anatomy, ultra-structure and metabolism are deeply affected by salt stress. Although salt mixtures occur naturally in soils there are few studies considering their effect in plant salt tolerance, particularly in halophytes. The aim of the present study was to determine the effects of the salt mixture Na2SO4 + NaCl at different concentrations on the anatomy of Prosopis strombulifera, and to compare them with the responses observed earlier in iso-osmotic monosaline cultures. Seedlings were grown hydroponically in Hoagland's solution adding salt pulses of NaCl + Na2SO4 (25 mM L-1 and 19 mM L-1, respectively), every 48 h until final Ψo values of -1, -1.9, and -2.6 MPa. Control plants were grown under unsalted conditions. The salt-mixture also induced anatomical and histological alterations in roots, stems and leaflets in comparison with control plants and monosaline treated plants. These changes were noticeable from Ψo = -1.9 MPa. Reduction in cortical tissues in roots and stems, and reduction in the mesophyll thickness were observed in treated plants, as well as lower number of leaflets. The different degrees of anatomical modifications were dependent on the organ/tissue analyzed and could be particularly attributed to the presence of Cl- or SO4 2- in the culture medium. Some of them developed features intermediate between those observed in monosaline (NaCl or Na2SO4) treated plants, in agreement with the reversion of the toxic effect of SO4 2- anion on plant growth under iso-osmotic salt-mixture. We propose that plant anatomical modifications are responses correlated with the chemical nature of the ions present in the medium. When Cl- and SO4 2- are simultaneously present in the solution, ionic interactions occur determining specific responses which differ in their degree or intensity from those caused by monosaline solutions.